Adherence to entecavir for chronic hepatitis B and correlation with effectiveness - Vanessa Romero Díaz-Maroto; Marina Sánchez Cuervo; Miguel Ángel Rodríguez Sagrado; Teresa Bermejo Vicedo (Farmacia Hospitalaria)
Purpose: to evaluate adherence of patients with chronic hepatitis B initiated on entecavir as first-line treatment and to correlate adherence with effectiveness. Methods: observational retrospective study performed between January 2007 and June 2013. Patients treated with entecavir for at least one year were included. A patient was considered to be adherent if median adherence was ≥ 95%. Virological response (HBV DNA < 20UI/ml by Polymerase Chain Reaction), biochemical response (normalized level of alanine amino transferase [AAT]) and serological response (loss of hepatitis B surface antigen [HBsAg]) was assessed at month 12. Results: 85 patients were included. The median adherence rate was 94.2 (SD 12.8)%. 85.7% of the adherent patients achieved a virological response in contrast with 71.4% of the nonadherent patients (OR:2,40; IC95%:0,60–9,54;p = 0,19). 87.9% of the adherent patients and 85.7% of the nonadherent patients showed normalized level of AAT (OR:1,21; IC95%:0,22- 6,60;p = 0,56). Two adherent patients showed clearance of hepatitis B surface antigen. Conclusion: the median adherence is not high. Nonadherent patients have a trend towards a higher rate of virological failure so it is necessary to promote improved adherence to treatment